Leemos un texto expositivo el celular en la vida de las personas - Sandoval Córdova, Claudia Jessica (2022)
The session entitled "We read an expositive text: Cell phone in people's lives ", was developed in Communication course, considering the competence reading various types of texts written in their mother language, from the required resources as the abilities, get information from the written text, infer and interpret information from the written text, reflect on and evaluate the form, content and context of the written text, it has been possible to achieve in the students the performance infers information, anticipating the content of the text, to starting from some clues (typography, index) and deducing the characteristics of people, characters, objects and places, as well as the meaning of words in context and expressions with figurative meaning, logical relationships (similarity difference and problem-solution) and hierarchical (main and complementary ideas), based on explicit and implicit information from the text. In the development of the session, motivating and challenging activities were applied that encouraged the children to build their capacities to understand any text they read and make deductions in a critical and creative way, appropriate to their respective situations of use. The pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, evaluation and transfer in the didactic processes of the area were taken into account. The learning strategies were consistent in the interests and needs of fifth grade of primary school students.